On Dense Subsemimodules and Prime Semimodules - Alwan, Ahmed H.; Alhossaini, Asaad M. A. (Iraqi Journal of Science, 2020)
In this paper, we study the class of prime semimodules and the related concepts, such as the class of semimodules, the class of Dedekind semidomains, the class of prime semimodules which is invariant subsemimodules of its injective hull, and the compressible semimodules. In order to make the work as complete as possible, we stated, and sometimes proved, some known results related to the above concepts.